The effect of music on patient anxiety undergoing bronchoscopy: a randomized controlled trial - Kacem Amani; Aissa Sana; Jomaa Wassim; Chebil Dhekra; Ben Jazia Rahma; Kharrat Imen; Benzarti Wafa; Knaz Asma; Ben Bedira Baraa; Gargouri Imen; Maatallah Anis; Abdelghani Ahmed (BMC Complementary Medicine and Therapies)
Abstract Background Bronchoscopy is a fundamental diagnostic and therapeutic examination with rare complications which is often associated to anxiety and discomfort. The aim of our study is to evaluate the effect of music on anxiety levels among patients undergoing bronchoscopy in the pneumology department. Methods We conducted a prospective, randomized, investigator-blinded, controlled trial performed in two university hospitals. The patients were randomized into two groups: experimental group who had preselected classic Tunisian music during bronchoscopy and control group who had bronchoscopy without music. we assessed anxiety level using Spilberger’s State Anxiety inventory (S-STAI) and comfort level using visual analogic scale (VAS). Vital signs and side effects during bronchoscopy were also assessed. Results One hundred thirty-six patients were equally assigned into the two groups. the anxiety levels before and after bronchoscopy were similar into the two groups. The music had no effect on anxiety level using the S-STAI . There was no significant difference between the two groups regarding side effects and vital signs during bronchoscopy. There was a significant effect of music on mean change of VAS score (p = 0.018). Conclusion The music improved comfort level of patients undergoing bronchoscopy. Trial registration This study was retrospectively registered in the pan African Clinical Trial Registry with the trial number PACTR202309620440045 on 3 September 2023.